Pilot-aided Joint Channel Estimation for OFDM Based Cooperative Multi-cell Networks - Yuan Wang; Zhongpei Zhang; Yixian Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Multi-cell joint channel estimation (JCE) is the basis for application of multi-cell cooperative processing. For weakness of the existing algorithms that power delay profile (PDP) knowledge of all multiple cells need be known or pilot sequence sets of all cells must be identical, in this paper, a pilot-aided time domain JCE algorithm is presented. And then, by using Generalized Akaike Information Criterion (GAIC) to estimate PDPs of all cells for reducing the signal space of channel estimation, the paper further optimizes this JCE algorithm. Simulation results show that the proposed algorithms have good mean square error (MSE) and corresponding space frequency block coded (SFBC) cooperative multi-cell transmission system has the good bit error rate (BER) performance too.